2021
DOI: 10.1017/s2040174420001300
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol levels in pregnancy as a possible determinant of fetal sex: a longitudinal study

Abstract: Stress during pregnancy has been widely studied and associated to different variables, usually with negative results for the health of the mother and the newborn, such as having a higher risk of suffering postpartum depression, premature birth, obstetrics complications or low birthweight, among others. However, there are not many lines of research that study the role that the sex of the baby plays on this specific stress and vice versa. Thus, the main objective was to analyse the relationship between the sex o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…For providing a methodological foundation for further investigations of HCC in pregnant samples, we investigated the bivariate influence of twenty-one pregnancy-related, sociodemographic, and hair-related covariates on HCC. The only covariates that showed a significant bivariate influence on HCC in at least two time points and in a consistent manner were maternal BMI, maternal education, difficulty accessing basic foods, and infant sex, which is partly consistent with previous studies 38 40 , 45 , 65 . For instance, we showed a significant difference in prenatal HCC by infant sex, whereby women giving birth to a female infant had significantly higher HCC preconception and in the first trimester, compared to women giving birth to a male infant.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For providing a methodological foundation for further investigations of HCC in pregnant samples, we investigated the bivariate influence of twenty-one pregnancy-related, sociodemographic, and hair-related covariates on HCC. The only covariates that showed a significant bivariate influence on HCC in at least two time points and in a consistent manner were maternal BMI, maternal education, difficulty accessing basic foods, and infant sex, which is partly consistent with previous studies 38 40 , 45 , 65 . For instance, we showed a significant difference in prenatal HCC by infant sex, whereby women giving birth to a female infant had significantly higher HCC preconception and in the first trimester, compared to women giving birth to a male infant.…”
Section: Discussionsupporting
confidence: 89%
“…The vast majority of previous studies did not find such an effect 33 , 38 , 39 , 44 , 61 , 66 73 . However, Romero-Gonzalez et al 65 recently reported significant differences in prenatal HCC by infant sex. Similar to our findings, they found a higher first-trimester HCC in women carrying a female compared to a male baby 65 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the association between maternal and infant HCC, several studies have provided interesting and sometimes conflicting results. Studies have shown a positive association between perceived stress and HCC in pregnant women, increased HCC in assisted reproductive technology, and increased HCC in the first trimester when a girl is carried to term ( 17 19 ). Regarding the mother–child relationship, one study found increased HCC in mothers with prolonged stress during pregnancy, but decreased HCC in their newborns ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy stage modifies the association between stress and birth sex‐ratio. Higher levels of maternal cortisol (measured in hair) at conception or during the first trimester are associated with relatively more female births (Romero‐Gonzalez et al, 2021 ). Male embryos of mothers stressed in the first week of pregnancy have an increased probability of chromosomal abnormalities associated with morbidity and mortality (Orzack et al, 2015 ; Ritchie & Roser, 2019 ).…”
Section: Introductionmentioning
confidence: 99%